Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal erusahaan Telekomunikasi (Studi Pada Perusahaan Telekomunikasi Yang Terdaftar Di Bursa Efek Indonesia Pada Periode Tahun 012-2015) - Damayanti, Fibriana, Kussudyarsana S.E., M.Si (2017)
This study aims to find empirical evidence of factors fecting the capital structure of telecommunication companies listed on the Indonesia Stock Exchange. Factors tested in this research are asset structure, ownership structure, business risk, and firm size. The sample of this study uses 5 telecommunication companies that are consistently listed in Indonesia Stock Exchange period 2012-2015. Sampling technique using purposive sampling technique or sampling based on certain considerations and criteria. The analytical method used is multiple linear regression analysis with first classical assumption test which includes normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. By testing the hypothesis using the test Significant simultaneous (F test) and partial test (t-Test) and Coefficient of Determination (R²) with standard error of estimate used at 5% or0.05. The result of the research identifies that the structure of assets, ownership structure and business risk significantly does not affect the company's capital structure, while firm size affects the capital structure of telecommunication companies listed in Indonesia Stock Exchange.